THE THEORETICAL PROBLEM OF THE IMAGE OF CHILD (Scientific journal of the Fergana State University, 2024)
This article provides a theoretical analysis of the artistic image and its nature. The manifestation of the image as an individualized generalization, in which things and events are a combination of particular features with the general aspects of the event, is explored. As tool that ensure the vitality of the artistic image, such elements of the image as the author’s description, portraiture, artistic psychologism and characteristic speech are studied.